2021
DOI: 10.3390/su13168866
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Reduction of Iron Ore with Hydrogen

Abstract: The steel industry represents about 7% of the world’s anthropogenic CO2 emissions due to the high use of fossil fuels. The CO2-lean direct reduction of iron ore with hydrogen is considered to offer a high potential to reduce CO2 emissions, and this direct reduction of Fe2O3 powder is investigated in this research. The H2 reduction reaction kinetics and fluidization characteristics of fine and cohesive Fe2O3 particles were examined in a vibrated fluidized bed reactor. A smooth bubbling fluidization was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 43 publications
2
23
0
2
Order By: Relevance
“…[17] The hydrogen-based process is characterized by a complex chemomechanical interplay of the different mechanisms involved, specifically the underlying reactions, mass transport, and volume changes. [18] Among the reaction steps, wüstite reduction to iron is the slowest one by nearly an order of magnitude lower reaction kinetics compared with the other two steps; therefore, it plays an important role in determining the overall rate of the reactions. [19] Now, many analytical models can be found in the literature in order to predict the kinetics behavior of direct reduction as a function of the many factors influencing the overall process.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The hydrogen-based process is characterized by a complex chemomechanical interplay of the different mechanisms involved, specifically the underlying reactions, mass transport, and volume changes. [18] Among the reaction steps, wüstite reduction to iron is the slowest one by nearly an order of magnitude lower reaction kinetics compared with the other two steps; therefore, it plays an important role in determining the overall rate of the reactions. [19] Now, many analytical models can be found in the literature in order to predict the kinetics behavior of direct reduction as a function of the many factors influencing the overall process.…”
Section: Introductionmentioning
confidence: 99%
“…A 0.05 m internal vibrated fluidized bed reactor was used. The advantages of using solar concentrated as a heat source were recently highlighted in number of publications with respect of solar-topower uses [23][24][25], solar-driven thermo-chemical reactions [4,25] and solar-driven physical applications [26][27][28]. Water/steam and N2 carrier gas were preheated in a coil heat exchanger within the cavity as illustrated at the right of the reactor in Figure 4.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…These COPs proclaimed the leading role of renewable energy in solving climate problems. The wider use of hydrogen was advocated [1,2] through, e.g., hydrogen-enriched natural gas [3], the direct reduction of iron ore [4], the use of hydrogen in the minerals' processing [5], and the production of CO 2 -based synthetic natural gas [6], among others. It is important to assess the ways that hydrogen production can help to meet the renewable energy goals.…”
Section: Introduction 1the Need To Develop H 2 Productionmentioning
confidence: 99%
“…According to Chen et al, 43 the oxygen release (step 2 of the reaction cycle) between layered Na(Mn 1/3 Fe 2/3 )O 2 and CO 2 is fairly slow and requires >3 h to be completed. 44,45 This was further investigated by TGA, where it was demonstrated that the reduction step preferably requires 4.5 to 6 h. Stoichiometrically, the yield should be 0.5 mol H 2 per mol MnFe 2 O 4 , which is only closely achieved for the coprecipitated reactant. Regrinding of the reactants between the cycles slightly increased the H 2 yield.…”
Section: The Mnfe 2 O 4 System In the Electrically Heated Furnacementioning
confidence: 99%